The role of the glycoprotein BCLB in the exosporium of Bacillus anthracis - Thompson, Brian M. (Kansas State University, 2007)
Anthrax is a highly fatal disease caused by the gram-positive, endospore-forming, rod-shaped bacterium Bacillus anthracis. Spores, rather than the vegetative bacterial cells, are the source of anthrax infections. The spores of B. anthracis are enclosed by a prominent loose-fitting structure called the exosporium. The exosporium is composed of a basal layer and an external hair-like nap. The filaments of the hair-like nap are made up largely of a single collagen-like glycoprotein called BclA. A second glycoprotein, BclB, has been identified in the exosporium layer. The specific location of this glycoprotein within the exosporium layer and its role in the biology of the spore are unknown. We created a mutant strain of B. anthracis ΔSterne that carries a deletion of the bclB gene. Immunofluorescence studies indicated that the mutant strain produced spores with increased amounts of the BclA glycoprotein expressed on their surface. Differences in exosporium composition between the mutant and wild-type spores were identified. The mutant was also found to possess structural defects in the exosporium layer of the spore (visualized by electron microscopy, immunofluorescence, and flow cytometry) resulting in an exosporium that is more fragile than that of a wild-type spore and is easily lost. The resistance properties of the mutant spores were unchanged from that of the wild-type spores. The bclB mutation did not affect spore germination or kinetics of spore survival within macrophages. BclB plays a key role in the formation and maintenance of a rigid and complete exosporium structure in B. anthracis. BclB plays a key role in the formation and maintenance of the exosporium structure in B. anthracis.
Keywords: Bacillus; anthracis; Biology, Microbiology (0410)